KEBUDAYAAN, PERUBAHAN SOSIAL, DAN AGAMA DALAM PERSPEKTIF ANTROPOLOGI - Kurnia Novianti (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2013)
As a discipline, anthropology raised ‘culture’ as a central concept that is widely discussed. In the process, ‘culture’ has very interesting dynamics, especially when used as an analytical tool in assessing change and religion issues. This paper argues about the dialectic of culture, change, and religion issues so that can explain the phenomena that observed in our daily lives. Through literatures and observation method, this paper aims to provide a perspective to understand the meaning of a phenomenon that observed and analyzed through the reveal of ‘hidden transcript’ behind the phenomenon.